Maturation of gastric electrical activity, gastric emptying and intestinal permeability in preterm newborns during the first month of life - Polimeno Lorenzo; Massimo Bisceglia; Salvia Gennaro; Montagna Osvaldo; Raimondi Francesco; Indrio Flavia; Riezzo Giuseppe; Cavallo Luciano; Francavilla Ruggiero (BMC, 2009)
Abstract Introduction Immaturity of motility, intestinal epithelial barrier function and absorptive capacity may play a role in the pathophysiology of intestinal diseases in preterms. We determined the gastric electrical activity and emptying, and intestinal permeability, in preterm newborns to verify if a maturation pattern exists in preterm newborns during the first month of life. Patients and methods Eighteen preterm newborns (median 34 wks, range 2 wks) completed the study. They underwent the recording of gastric electrical activity by means of cutaneous electrogastrography, the ultrasound examination of gastric emptying, and the lactulose-to-mannitol ratio from permeability-absorption test on days 3, 7, 15, and 30 after birth. Results Gastric electrical activity and emptying showed only slight changes between day 3 and day 7. On the contrary, an evident maturation in permeability, expressed as L/Mratio, was evident over time (Friedman Repeated Measures Analysis, p = 0.004). Conclusion In preterm healthy newborns of 34 weeks gestational age, electrical and motor activity are completely developed at birth whilst the intestinal epithelial barrier clearly improves during the first week of life.